Self-Productivity in Early Childhood - Friedhelm Pfeiffer; Katja Coneus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Self-productivity is a crucial feature in the process of skill formation. It means that skills and health acquired at one stage in the life cycle enhance skills and health formation at later stages. This paper presents an empirical investigation of self-productivity in early childhood in Germany. The data are drawn from the mother-child questionnaire of the German Socio-Economic Panel for the birth cohorts 2002-2005. The magnitude of self-productivity varies between skills and over time. A one percent increase in birth weight increase child's noncognitive skills by 0.34 percent and child's health by 0.64 percent at the age of 3-18 months. Until the age of 42 months a one percent increases in child's noncognitive skills enhances child's verbal skills by 0.57 percent and child's everyday skills by 1.04 percent. Furthermore, our estimates suggest synergies between child's health and child's noncognitive skills.
Older version: http://hdl.handle.net/10419/24624
Keywords: I20; J13; J24; 330; self-productivity; early childhood; skill formation; birth weight; health; Kinder; Gesundheit; Qualifikation; Bildungsniveau; Schätzung; Deutschland